A Novel Fragmentation Sensitivity Index Determines the Susceptibility of Red Blood Cells to Mechanical Trauma - Ugurel, Elif; Goksel, Evrim; Goktas, Polat; Cilek, Neslihan; Atar, Dila; Yalcin, Ozlem (Frontiers in physiology, 2021)
Supraphysiological shear stresses (SSs) induce irreversible impairments of red blood cell (RBC) deformability, overstretching of RBC membrane, or fragmentation of RBCs that causes free hemoglobin to be released into plasma, which may lead to anemia. The magnitude and exposure tisme of the SSs are two critical parameters that determine the hemolytic threshold of a healthy RBC. However, impairments in the membrane stability of damaged cells reduce the hemolytic threshold and increase the susceptibility of the cell membrane to supraphysiological SSs, leading to cell fragmentation. The severity of the RBC fragmentation as a response to the mechanical damage and the critical SS levels causing fragmentation are not previously defined. In this study, we investigated the RBC mechanical damage in oxidative stress (OS) and metabolic depletion (MD) models by applying supraphysiological SSs up to 100 Pa by an ektacytometer (LORRCA MaxSis) and then assessed RBC deformability. Next, we examined hemolysis and measured RBC volume and count by Multisizer 3 Coulter Counter to evaluate RBC fragmentation. RBC deformability was significantly impaired in the range of 20–50 Pa in OS compared with healthy controls ( p < 0.05). Hemolysis was detected at 90–100 Pa SS levels in MD and all applied SS levels in OS. Supraphysiological SSs increased RBC volume in both the damage models and the control group. The number of fragmented cells increased at 100 Pa SS in the control and MD and at all SS levels in OS, which was accompanied by hemolysis. Fragmentation sensitivity index increased at 50–100 Pa SS in the control, 100 Pa SS in MD, and at all SS levels in OS. Therefore, we propose RBC fragmentation as a novel sensitivity index for damaged RBCs experiencing a mechanical trauma before they undergo fragmentation. Our approach for the assessment of mechanical risk sensitivity by RBC fragmentation could facilitate the close monitoring of shear-mediated RBC response and provide an effective and accurate method for detecting RBC damage in mechanical circulatory assist devices used in routine clinical procedures.